1996
DOI: 10.5694/j.1326-5377.1996.tb124957.x
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle riding and oral/maxillofacial trauma in young children

Abstract: Objectives To investigate the frequency of oral/maxillofacial injuries in children who have had a bicycle incident and to relate this to the wearing of a protective helmet. Design Part of a larger prospective study in which self‐administered questionnaires were completed by each child with bicycle‐related injuries and their parents or caregivers. Setting Two tertiary‐referral children's hospitals (between 1 April 1991 and 30 June 1992) and three general hospitals (between 1 August 1991 and 30 June 1992) in Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 15 publications
5
31
1
Order By: Relevance
“…The design of currently available helmets may reduce the risk of head and midface injury. However, they may not provide enough protection against mandibular fractures 1,118 .…”
Section: Preventive Measuresmentioning
confidence: 98%
See 1 more Smart Citation
“…The design of currently available helmets may reduce the risk of head and midface injury. However, they may not provide enough protection against mandibular fractures 1,118 .…”
Section: Preventive Measuresmentioning
confidence: 98%
“…Mandibular fractures are the most common facial fractures seen in hospitalized children 1,11,12,21,32,53,55,70,88,90,96,107,117,134 . Their incidence increases with age 28,45,90,96 .…”
Section: Site and Patternmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] One of the untoward results of bicycle use is head injuries. Recent legislation made the use of helmets mandatory for all bicyclists in British Columbia starting in September 1996.…”
mentioning
confidence: 99%
“…Thompson et al (22) reported helmets as protective against upper and mid facial injuries, but showed its ineffectiveness against lower facial injuries. Similarly, Acton et al (26) showed that helmets did not prevent maxillofacial injuries among children, and suggested t that the design of the helmets be modified.…”
Section: Discussionmentioning
confidence: 97%